Semi-Symmetric Metric Connection on Homothetic Kenmotsu Manifolds - Thangmawia, L.; Kumar, R. (Journal of Scientific Research, 2020)
The object of the paper is to study homothetic Kenmotsu manifold with respect to semi-symmetric metric connection. We discuss locally -symmetric homothetic Kenmotsu manifold and -projectively flat homothetic Kenmotsu manifold with respect to semi-symmetric metric connection. Finally, we construct an example of 3-dimensional homothetic Kenmotsu manifold to verify some results.